Hepatoprotective Effects of Zataria Multiflora Ethanolic Extract on Liver Toxicity Induced by Cyclophosphamide in Mice - Shokrzadeh, M.; Chabra, A.; Ahmadi, A.; Naghshvar, F.; Habibi, E.; Salehi, F.; Assadpour, S. (Drug Research, 2015)
Although cyclophosphamide (CP), an alkylating agent, has been extensively used in chemotherapy, it possesses a wide spectrum of adverse effects including hepatotoxicity. This study was aimed to evaluate the protective effects of Zataria multiflora against hepatic damage induced by CP in mice.Mice were orally (gavages) pretreated with the ethanolic extract aerial parts of Zataria at doses of 50, 100, 200, or 400 mg/kg for 7 consecutive days before a single intraperitoneal injection of 200 mg/kg CP. After 24 h, animals were anesthetized, blood samples and hepatic tissues were collected and used for biochemical and histological examination.Serum levels of hepatic markers were significantly increased after only CP treated animals but restored in Zataria pretreated groups. A single dose of CP administration also markedly induced abnormality in the levels of several biomarkers associated with oxidative stress in liver tissues homogenates. However, pretreatment with Zataria significantly inhibited the abnormality of antioxidant enzymes defense system in the liver tissues. In addition, histopathological studies proved that CP causes damage to the liver, and this was evidenced by the induced dilated and congested sinusoidal space, lymphocytic infiltration between hepatocytes, portal space with moderate to severe inflammation and necrotic hepatocyte with absence of nuclei. Zataria effectively protected animals against CP-induced hepatic tissue damages.Our results reveal that Zataria produces a potent hepatoprotective role and could be a potent candidate to use concomitantly as a supplement agent against hepatotoxicity of CP for the patients undergoing chemotherapy.
Keywords: hepatoprotective; zataria multiflora; cyclophosphamide; liver toxicity; antioxidant activity